2022
DOI: 10.1681/asn.2021020140
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α5 Is Regulated by miR-218-5p in Endothelial Progenitor Cells

Abstract: Background Endothelial cell injury is a common nidus of renal injury in patients and consistent with the high prevalence of acute kidney injury reported during the COVID-19 pandemic. This cell type expresses integrin α5 (ITGA5), which is essential to the Tie2 signaling pathway. The micro-RNA miR-218-5p is upregulated in endothelial progenitor cells following hypoxia, but miRNA regulation of Tie2 in the endothelial progenitor cell (EPC) lineage is unclear. Methods We isolated EPCs derived from the human kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The regulatory network between miR-192-5p and FTO gives us an idea of treating renal injury, and they might be promising targets for renal I/R injury-induced AKI therapy.miRNAs are important in the maintenance of normal cellular functions, and dysregulation of miRNAs can result in a number of pathological states. Several studies have reported that miRNAs regulate angiogenesis, mitochondrial dysfunction, endothelial progenitor cell migration, and glomerular basement membrane structure [ 8 , 9 , 32 , 33 ]. A previous study also reported that miR-192-5p inhibition blocks cell apoptosis in vancomycin-induced HK-2 cells [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulatory network between miR-192-5p and FTO gives us an idea of treating renal injury, and they might be promising targets for renal I/R injury-induced AKI therapy.miRNAs are important in the maintenance of normal cellular functions, and dysregulation of miRNAs can result in a number of pathological states. Several studies have reported that miRNAs regulate angiogenesis, mitochondrial dysfunction, endothelial progenitor cell migration, and glomerular basement membrane structure [ 8 , 9 , 32 , 33 ]. A previous study also reported that miR-192-5p inhibition blocks cell apoptosis in vancomycin-induced HK-2 cells [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, endothelial-specific miR-17, -18a, -19a, -20a, -19b-1, and -92a-1 knockout promotes renal dysfunction following renal I/R injury through dysfunction of renal microvasculature [ 8 ]. Another study found that miR-218-5p promoted endothelial cell injury to accelerate renal injury [ 9 ]. Kirti et al.…”
Section: Introductionmentioning
confidence: 99%
“…As precursors of endothelial cells, endothelial progenitor cells (EPCs) are derived mainly from peripheral blood and bone marrow [ 37 ]. They play a pivotal role in disorders related to endothelial damage by proliferating, migrating, and differentiating into endothelial cells, in addition to secreting a range of cytokines and vascular growth factors [ 38 ]. Generally, EPCs are separated, based on their morphological traits and culture duration, into two categories: early myeloid angiogenic cells and late endothelial colony-forming cells [ 39 ].…”
Section: Endothelial Cells Orchestrate Angiogenesis–osteogenesis Coup...mentioning
confidence: 99%